Integrated analysis of seismic attributes and well-logs in reservoir characterization: seismic-facies classification and reservoir facies mapping - Rijfkogel, Luke (Kansas State University, 2020)
Carbonate reservoir characterization introduce challenges that constantly require updates based on new seismic and production data. Understanding the connection between seismic response and litho-petrophysical properties is a crucial component to producing tangible results in hydrocarbon reservoir characterization, particularly in carbonate reservoirs. Applying models in seismic interpretation is essential to integrating data from a variety of disciplines including geology, geophysics, petrophysics and reservoir engineering. In this study, three post-stack seismic attributes (instantaneous bandwidth and peakedness along with volume attributes such as Root Mean Square - RMS energy) are used to distinguish and identify seismic classes pertaining to variations in litho/petrophysical facies from the Mississippian saline aquifer hosted in a carbonate reservoir from the Wellington Field, Sumner County, Kansas. Neutron porosity, bulk density, and sonic well logs provided a correlation with seismic amplitude, which in turn reflects reservoir properties associated to acoustic impedance. Neutron porosity logs were characterized into three classes. Class one representing a porosity less than eight percent, Class two representing a porosity class of greater than eight and less than twelve percent and Class three representing a porosity greater than twelve percent. The impedance differences across a seismic reflector are the controlling parameter of reflectivity. By having seismic and well log data sets provide the connection to characterize the reservoir to be modeled for porosity prediction based on amplitude and seismic facies classification for the effects of enhanced oil recovery (EOR) or geological sequestration of CO₂. Using an unsupervised neural network and selecting three facies classes to correlate with three petrophysical classes. Three well-log classes are defined to describe the reservoir in terms of porosity using neutron porosity well logs. Seismic facies three has the highest porosity (greater than 12 percent), landed in structurally low areas and likely resemble dolomite prone area. The second-facies has porosity between 7 and 13 percent resemble a transitional zone from structurally low to high showing reworked brecciated limestone facies from CT scans. Seismic facies one has porosity less than 11 percent and resemble a structurally high erosional area. The seismic facies prediction map was constructed by correlating reservoir porosity using neutron porosity logs and seismic amplitude attributes in a carbonate reservoir. Due to the nature of elastic properties and mineralogy of carbonates that render the reservoir porosity the most significant factor controlling amplitude variation. Seismic amplitude attributes (bandwidth, peakedness, and RMS energy) reveal some unexpected features interpreted as small-scale faults associated with the Nemaha Uplift. Using the same three attributes as an input for an unsupervised neural network and selecting three seismic facies produces results that correlate with one out of the three porosities, providing a correlation between well-logs and seismic amplitude that can be used to predict reservoir facies in terms of porosity especially for higher porous zones. A CT scan of the top of Wellington KGS #1-32 core indicates slit-shaped (fracture) porosity and vuggy porosity dominate at the top of the reservoir. The bottom of the reservoir is dominated by fractured porosity ranging from 1.1 mm to 0.1 mm in size. The slit-shaped porosity is orientated vertically while the vuggy porosity was located within the diagenetic dolomite which was contained within the chert. Wellington KGS #2-32 core is dominated by slit-shaped porosity ranging in size from 0.4mm to 0.07mm. Slit shaped porosity shown from the middle CT scan in the Wellington KGS #2-32 shows faulting is associated after diagenesis of the dolomite. The vuggy porosity are the result from diagenetic processes and the slit-shaped porosity is associated to faulting from the Nemaha Uplift. This study illustrates the ability to use a data driven approach to an unsupervised neural network to identify seismic facies that relate to porosity classes by integrating well-logs, seismic attributes, and CT scans to characterize a carbonate petroleum reservoir system.
Keywords: Seismic attributes; Reservoir characterization; Geophysical well logs; Reflection seismology; Seismic facies